Purification and characterization of the first gamma-phospholipase inhibitor (gamma PLI) from Bothrops jararaca snake serum - Serino-Silva, Caroline; Morais-Zani, Karen; Toyama, Marcos Hikari [UNESP]; Toyama, Daniela de Oliveira [UNESP]; Gaeta, Henrique Hesse [UNESP]; Bittencourt Rodrigues, Caroline Fabri; Aguiar, Weslei da Silva; Tashima, Alexandre Keiji; Grego, Kathleen Fernandes; Tanaka-Azevedo, Anita Mitico (Public Library Science, 2018)
Phospholipases A(2) (PLA(2)) are enzymes acting on the cell membrane phospholipids resulting in fatty acids and lysophospholipids and deconstructing the cell membrane. This protein is commonly found in snake venoms, causing tissue inflammation in the affected area. Evidence indicates that snakes have natural resistance to their own venom due to protective properties in plasma, that inhibit the action of proteins present in their venom. Given that, this study aimed to purify and characterize a gamma PLI from Bothrops jararaca serum, named gamma BjPLI. PLA(2) inhibitor was isolated using two chromatographic steps: an ion exchange column (DEAE), followed by an affinity column (crotoxin coupled to a CNBr-activated Sepharose resin). The purity and biochemical characterization of the isolated protein were analyzed by RP-HPLC, SEC, SDS-PAGE, circular dichroism and mass spectrometry. The ability to inhibit PLA(2) was determined by enzymatic activity, neutralization of paw edema and myonecrosis. The protein purity was confirmed by RP-HPLC and SEC, whilst an apparent molecular mass of 25 kDa and 20 kDa was obtained by SDS-PAGE, under reducing and non-reducing conditions, respectively. According to mass spectrometry analysis, this protein showed 72% and 68% of coverage when aligned to amino acid sequences of two proteins already described as PLIs. Thus, the inhibitory activity of enzymatic, edema and myonecrotic activities by gamma BjPLI suggests a role of this inhibitor for protection of these snakes against self-envenomation.